MEDIA SOSIAL SEBAGAI FAKTOR PENGARUH TERHADAP KEPEKAAN SOSIAL - M. Fadlan Choiri; Firman, Firman; Netrawati, Netrawati (Liberosis: Jurnal Psikologi dan Bimbingan Konseling, 2024)
Social media has become an integral part of modern society, including university students as agents of change. This study aims to explore the relationship between social media usage intensity and students' social sensitivity. Using a qualitative method literature study, this research analyzes findings from previous studies on social media usage and its impact on students' social capabilities. The results indicate that social media intensity influences students' social sensitivity, both positively and negatively. While social media fosters social participation, excessive usage reduces direct interaction and social empathy. This study highlights the importance of digital literacy and campus synergy in developing students' social sensitivity to address the challenges of modern society.